Arbeit transformieren! Denkanstöße der Kommission "Arbeit der Zukunft" - Jürgens, Kerstin (Forschung aus der Hans-Böckler-Stiftung, 2017)
In the next decades the working world will change fundamentally. What powers affect the labor market? What changes are to be expected? And what does that mean for those involved in labor politics? This conclusive report by the Commission "Work in the Future" - with members from the fields of science, businesses and unions as well as practitioners - presents a diagnosis of the current situation and provides a perspective of the future of work. Particularly, however, the commission offers food for thought on the question how society can master the fast changes so that work in the digital economy guarantees the participation in society and more than mere livelihood.